Konsep Dasar Administrasi Pendidik dan Tenaga Kependidikan di Era Society 5.0 - Dessy Rahma Putri; A’zima Ashari Fauzi; Ahmad Sabri; Rully Hidayatullah (Journal Innovation In Education, 2024)
In the Society 5.0 era, the administration of educators and educational staff faces new challenges due to the rapid development of technology and changing human resource demands. This study aims to formulate a basic concept of educator and educational staff administration that aligns with the dynamics of the digital age. Through a literature review method, data was collected from various sources, including books, journals, and other relevant references. This research thoroughly examines the definition of educator and educational staff administration, the processes involved, and the role of teachers in administrative management within the Society 5.0 era. Findings indicate that the administration of educators and educational staff needs to adopt an approach based on information technology, enhance cross-sector collaboration, and focus on developing educator competencies to meet the challenges of globalization and digitalization. This article provides guidance on how to understand, address, and anticipate issues in educational administration in this modern era.